The Teacher as Learner: Professional Development Programs as Agents for Change - Penelope Little; Margaret McMillan (Halla Newcastle Education and Research Center, 2019)
Purpose To provide a rationale for the design and implementation of a Professional Development Program for academics and present reflections on the process and outcomes provided by the program facilitators and participants. Methods The program methodology centres on a collaborative approach to professional development. However, the focus is on student-centred rather than teacher-centred learning approaches in a manner consistent with the ideals of practice/problem-based learning philosophy and methodology. Results Reflective pieces provided at the conclusion of the program demonstrated that participants satisfied the criteria for leaner-managed learning outcomes. Conclusion The context and culture of the academic environment has continuously changed over the last three decades mainly given developments in technology. However, in contexts reliant on technology enhanced learning and teaching, successful on-line learning events still need to reflect a student-centred approach. In most instances professional development opportunities should allow academics the freedom to pursue answers to their own development needs.